Anti-oxidant and Anti-inflammatory Effects of Aquatic Exercise in Allergic Airway Inflammation in Mice - Lee, Boae; Kim, Yeonye; Kim, Young Mi; Jung, Jaehoon; Kim, Taehyung; Lee, Sang-Yull; Shin, Yong-Il; Ryu, Ji Hyeon (Frontiers in Physiology, 2019)
Oxidative stress and inflammation are key pathways responsible for the pathogenesis of asthma. Aquatic exercise (AE) has been proven to elicit a variety of biological activities such as anti-oxidant and anti-inflammatory effects. However, although proper forms of AE provide beneficial health effects, incorrect forms and types of AE are potentially injurious to health. Several studies have investigated AE, but the relationship between types of AE and asthma has not been fully elucidated. This study evaluated the effects of two types of AE according to resistance on ovalbumin (OVA)-induced allergic airway inflammation in mice. BALB/c mice were subjected to OVA sensitization and challenge, and then to different types of AE including, walking and swimming, in a pool filled with water to a height of 2.5 cm and 13 cm for 30 min, respectively. AE reduced OVA-induced eosinophilic inflammation, airway hyperresponsiveness, and serum immunoglobulin E level. AE significantly inhibited increases in interleukin (IL)-4, IL-5, IL-13, histamine, leukotriene D4, and tryptase levels in bronchoalveolar lavage fluid (BALF). AE also effectively suppressed mucus formation, lung fibrosis, and hypertrophy of airway smooth muscle within the lung tissues. This exercise markedly reduced the levels of malondialdehyde while increased glutathione and superoxide dismutase activity in lung tissues. Furthermore, AE significantly decreased tumor necrosis factor-α, IL-6 levels, and prostaglandin E2 production in BALF. The inhibitory effects of swimming on the levels of biomarkers related to oxidative stress and inflammation were greater than that of walking. These effects may have occurred through upregulation of NF-E2-related factor 2/heme oxygenase-1 signaling and suppression of mitogen-activated protein kinase/nuclear factor-κB pathway. Cumulative results from this study suggest that AE might be beneficial in mitigating the levels of biomarkers related to oxidative stress and inflammation. Thus, this therapy represents a crucial non-pharmacological intervention for treatments of allergic airway inflammation.